Dwie koncepcje badań metafizycznych rozwijane w XX wieku w filozofii polskiej - Marciniak, Dominik (Człowiek i Społeczeństwo, 2022)
The paper presents two different conceptions of metaphysics – scientistic and neoscholastic – developed in the 20th century by, among others, Polish philosophers: Stanisław Kamiński, Mieczysław Gogacz, Tadeusz Czeżowski and Zygmunt Zawirski. These authors refer to the problem of the possibility of conducting metaphysical research in contemporary philosophy. In this context, they examine issues such as the method, subject, and specificity of research carried out within metaphysics. In the summary, the discussed conceptions are compared with each other. The basic issues determining the similarities and differences between respective positions are the problem of the autonomy of metaphysics in relation to other sciences and the issue of the starting point (source of preliminary data) of metaphysical research. Findings regarding the latter issue turn out to be crucial for resolving the question of the appropriate model for research in metaphysics.